1993
DOI: 10.1121/1.405838
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of deep ocean noise (0.4–30 Hz) with wind, and the Holu Spectrum—A worldwide constant

Abstract: One year of ambient ocean noise data, 0.4 to 30 Hz, from the Wake Island hydrophone array in the northwestern Pacific are compared to surface wind speeds, 0–14 m/s (0–28 kn). Between 0.4 and 6 Hz, noise levels increase with wind speed at rates of up to 2 dB per m/s until a saturation is reached having a slope of about −23 dB/octave and a level of 75 dB relative to 1 μPa/√Hz at 4 Hz. This noise saturation, called the ‘‘Holu Spectrum,’’ likely corresponds to saturation of short-wavelength ocean wind waves. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 0 publications
6
69
0
Order By: Relevance
“…8). The data from this study are not directly comparable to the McCreery et al (1993) analysis because the previous study removed loud transient signals (earthquakes, close ships, seismic airgun activity) with a power level at least 3 dB greater than the level of the two adjacent samples in the time series, whereas the spectra presented in Fig. 8 include all transients.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…8). The data from this study are not directly comparable to the McCreery et al (1993) analysis because the previous study removed loud transient signals (earthquakes, close ships, seismic airgun activity) with a power level at least 3 dB greater than the level of the two adjacent samples in the time series, whereas the spectra presented in Fig. 8 include all transients.…”
Section: Discussionmentioning
confidence: 58%
“…Although this work showed a recent decreasing trend in specific components of low frequency sound levels at Wake Island, it is likely that there has been an overall increase compared to the early 1980s (McCreery et al, 1993) (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
“…The noise at the southern hydrophone, U26, may differ because the instrument is deeper than the others. McCreery et al (1988 and1993) has found from using hydrophones near Wake Island that the noise levels between 3 and 6 Hz do not vary much with depth. They do see differences in the 10 to 20…”
Section: Instrumentationmentioning
confidence: 99%
“…, sound in the deep ocean is almost invariant (McCreery et al 1993). This is taken to indicate that, at any wave frequency 0.5 , f w , 5 Hz (6.5 , l , 0.06 m), the wavenumber spectrum under these conditions is both isotropic in direction and also constant in amplitude.…”
mentioning
confidence: 99%